1977
DOI: 10.1007/bf02669340
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gas bubbles injected into molten metals under laminar flow conditions

Abstract: Velocity and volume measurements of gas bubbles injected into liquid metals under laminar flow conditions (at the orifice) have been achieved. A novel experimental approach utilizing noises generated by bubbles was used to collect the necessary data. Argon gas was bubbled through tin, lead, and copper melts, and gas bubble formation frequencies (and hence bubble sizes) were determined. It was found that the bubble size generated for a particular orifice diameter was dependent upon the magnitudes of the orifice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…The discussion is based on previous cineradiographic observations of bubbles forming in liquid metal systems [6] systems [2][3][4] J. In the present work, the non-wetting characteristics ofliq uid metals are shown to be of signifificant importance in many metallurgical bubbling systems.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…The discussion is based on previous cineradiographic observations of bubbles forming in liquid metal systems [6] systems [2][3][4] J. In the present work, the non-wetting characteristics ofliq uid metals are shown to be of signifificant importance in many metallurgical bubbling systems.…”
mentioning
confidence: 73%
“…Recent results obtained by several investigators [2][3][4] are shown in Fig. 1 for six different liquid metals.…”
Section: Constant Frequency Phenomenonmentioning
confidence: 91%
See 3 more Smart Citations